Conjunctivo Corneal Intraepilheleal Neoplasia-Invasive Squamous Cell Carcinoma of Middle Age Group People (TAJ: Journal of Teachers Association, 2011)
Conjunctivo corneal intra epithelial neoplasia and invasive squamous cell carcinoma is rare but not uncommon it involve older patient1. Here we get two cases of middle age group patient suffering from invasive squamous cell carcinoma. Intra epithelial neoplasia is a precancerous condition may turn into invasive squamous cell carcinoma when invade the basement membrane. These are vision threatening even life threatening condition. The slightest sign of recurrence with invasive squamous cell carcinoma the eye must be excised and if recurrence takes place, the orbit must be exenterated and radiation therapy should be given2. So early diagnosis and proper management is important. In this article two cases of well differentiated invasive squamous cell carcinoma confirmed by histopathological report of middle aged group people and their management are presented. There is no recurrence after five years of treatment. So invasive squamous cell carcinoma may occur in middle age group people and histopathological test may require in all suspicious cases of abnormal growth of limbal conjunctiva specially pterygium like growth with a different presentation.TAJ 2011; 24(1): 51-53